In my kitchen : a collection of new and favorite vegetarian recipes - Madison, Deborah (Ten Speed Press, 2017)
Presents an updated collection of recipes from the country's leading authority on vegetarian cooking, including such dishes as cheese souffle, braised summer vegetables, and zucchini cake, with menu suggestions and tips for modifications.